Does intra-lumbar flexion during lifting differ in manual workers with and without a history of low back pain? A cross-sectional laboratory study. Issue 10 (3rd October 2022) - Saraceni, Nic; Campbell, Amity; Kent, Peter; Ng, Leo; Straker, Leon; O'Sullivan, Peter
Abstract: Advice to limit or avoid a flexed lumbar curvature during lifting is widely promoted to reduce the risk of low back pain (LBP), yet there is very limited evidence to support this relationship. To provide higher quality evidence this study compared intra-lumbar flexion in manual workers with ( n = 21) and without a history of LBP ( n = 21) during a repeated lifting task. In contrast to common expectations, the LBP group demonstrated less peak absolute intra-lumbar flexion during lifting than the noLBP group [adjusted difference −3.7° (95%CI −6.9 to −0.6)]. The LBP group was also further from the end of range intra-lumbar flexion and did not use more intra-lumbar range of motion during any lift condition (both symmetrical and asymmetrical lifts and different box loads). Peak absolute intra-lumbar flexion was more variable in the LBP group during lifting and both groups increased their peak absolute intra-lumbar flexion over the lift repetitions. This high-quality capture of intra-lumbar spine flexion during repeated lifting in a clinically relevant cohort questions dominant safe lifting advice. Practitioner summary: Lifting remains a common trigger for low back pain (LBP). This study demonstrated that people with LBP, lift with less intra-lumbar flexion than those without LBP. Providing the best quality in-vivo laboratory evidence, that greater intra-lumbar flexion is not associated with LBP in manual workers, raising questions about lifting advice.